OPTIMASI VOLUME LARUTAN PREKURSOR NATRIUM SILIKAT HASIL PENGOLAHAN ABU SEKAM PADI TERHADAP KELENTURAN PLASTIK KOMPOSIT SILIKA TERIMOBILISASI EDTA-AG DAN KITOSAN - Martha C.W Ndoen; Hermania Em Wogo (Fakultas Pertanian, Universitas Timor, 2020)
It has been done a study, which it aims to know the volume optimazation of precursor solution sodium silicate as a product of rice husk ash processing to the flexibility of EDTA-Ag and chitosan immobilized silica composite plastics. The silica used in this study was a destruction product of rice husk processing. the silica content in rice husk used in this experiment was 93.608 %. The solution volume of sodium silicate used was 10, 30 dan 50 mL. Meanwhile, the chitosan variations used were 0.3 and 0.7 gram. The test result of surface area with a titration method exhibited that the highest surface acidity of EDTA-Ag immobilized silica is 3,4 mmol/g at the volume of sodium silicate 30 mL. While, the area of optimum surface using a blue methyilene is 17,61131 m2/g for the volume of sodium silicate 30 mL at the contact time 80 minutes. Based on characterization result using FTIR, EDTA-Ag immobilized silica has been synthesized contains Si-OH groups from the gel silica (1083.92 cm-1), -CH2- group (1384.79 cm-1) and –NHCOCH3 group from EDTA (1639.38 cm-1). It was done a for mechanical test of plastics from EDTA-Ag and chitosan immobilized silica composite, the highest elongation percentage was obtained, namely 27,5 % at the chitosan variation 0.3 gram.